An amphibian toxin phenotype is sexually dimorphic and shows seasonal concordant change between sexes - Frey, Anna R.; Bucciarelli, Gary M.; Hu, Daniel D.; Kats, Lee B.; Green, David B. (Frontiers in Amphibian and Reptile Science, 2023)
Sexually dimorphic phenotypes are consequential to animal survival, and this is especially apparent with defense phenotypes. Amphibians have poison glands, and several lineages maintain a neurotoxin, tetrodotoxin (TTX) that is largely considered a derived chemical defense trait. However, production pathways are unclear and as such, whether males and females differentially produce or appropriate toxin concentrations is not known. We evaluated the relationship between TTX concentrations, sex, and morphology by collecting trait data from more than 850 wild newts of the genus Taricha and tested for sex-based differences, potential sex-based change to the phenotype between breeding seasons, and factors influencing toxicity. Females, regardless of reproductive status exhibited greater concentrations than males and temporal patterns indicate male and female trait values tend to fluctuate concordantly at short time scales, with females showing greater change over time. Tree regression results underscored the importance of size and sex to the phenotype. Sexual dimorphism and plasticity of toxins broadens the ecological roles of animal poisons beyond defense only and should recast how we model the evolution of tetrodotoxin.